Fundamental Approach to Discrete Mathematics - Acharjya, D.P; Sreekumar (New Age International Ltd, 2009)
About the Book: The book `Fundamental Approach to Discrete Mathematics` is a required part of pursuing a computer science degree at most universities. It provides in-depth knowledge to the subject for beginners and stimulates further interest in the topic. The salient features of this book include: Strong coverage of key topics involving recurrence relation, combinatorics, Boolean algebra, graph theory and fuzzy set theory. Algorithms and examples integrated throughout the book to bring clarity to the fundamental concepts. Each concept and definition is followed by thoughtful examples. User-friendly and accessible presentation to make learning more interesting as much as possible without compromising mathematical rigour. Includes glossary of all symbols discussed in the book together with the chapter where each was introduced. Around 300 complete solved illustrations to explain the concepts. Over 300 end-of-chapter exercises are included to stimulate further interest in the subject. Contents: Mathematical Logic Set Theory Binary Relation Function Generating Function and Recurrence Relation Combinatorics Group Theory Codes and Group Codes Ring Theory Boolean Algebra Introduction to Lattices Graph Theory Tree Fuzzy Set Theory.